2017
DOI: 10.31235/osf.io/ewa8b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nation-building, industrialisation, and spectacle: Political functions of Gujarat’s Narmada pipeline project

Abstract: Since 2000 the Indian state of Gujarat has been working to construct a state-wide water grid to connect 75% of its approximately 60 million urban and rural residents to drinking water sourced from the controversial Sardar Sarovar Dam on the Narmada River. This project represents a massive undertaking – it is billed as the largest drinking water project in the world – and is part of a broader predilection toward large, concrete-heavy supply-side solutions to water insecurity across present-day India. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Politicians also perform and engage in these processes of spectacle and nation‐building (Luxion, 2017; Schwenkel, 2015). In a case from Gujarat, India, Luxion (2017) showed how the construction of the Narmada pipeline was a chance for the state to leverage a national project to showcase modernity, state power and national identity through displays of ‘spectacle’ (see also P. Harvey & Knox, 2015; Schwenkel, 2015). These ideas become “encoded” (Jasanoff & Kim, 2015, p. 20) in material technologies when engineers and politicians decide to harness the infrastructure to provide more water to certain places, while denying it to others (see also Star, 1999).…”
Section: Big Water Infrastructure Scholarship: Taking Stock and Synth...mentioning
confidence: 99%
See 2 more Smart Citations
“…Politicians also perform and engage in these processes of spectacle and nation‐building (Luxion, 2017; Schwenkel, 2015). In a case from Gujarat, India, Luxion (2017) showed how the construction of the Narmada pipeline was a chance for the state to leverage a national project to showcase modernity, state power and national identity through displays of ‘spectacle’ (see also P. Harvey & Knox, 2015; Schwenkel, 2015). These ideas become “encoded” (Jasanoff & Kim, 2015, p. 20) in material technologies when engineers and politicians decide to harness the infrastructure to provide more water to certain places, while denying it to others (see also Star, 1999).…”
Section: Big Water Infrastructure Scholarship: Taking Stock and Synth...mentioning
confidence: 99%
“…In doing so, engineers develop "infrastructural knowledge" of designing, constructing and operating water infrastructure, both of which are infused with state goals of development and free-market ideology (Björkman, 2015). Politicians also perform and engage in these processes of spectacle and nation-building (Luxion, 2017;Schwenkel, 2015). In a case from Gujarat, India, Luxion (2017) showed how the construction of the Narmada pipeline was a chance for the state to leverage a national project to showcase modernity, state power and national identity through displays of 'spectacle' (see also P. Harvey & Knox, 2015;Schwenkel, 2015).…”
Section: Infrastructural Knowledge Practices and Subjectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Simply put, the municipal corporation, having decreased its reliance on groundwater, needs to be disentangled from larger assumptions around the decrease in groundwater use across the city. This, in turn, calls into question the rationale behind bringing Narmada waters to Ahmedabad to begin with, and the logic of the Sardar Sarovar Dam and the Narmada Pipeline Project in extension (see [61] for more on this).…”
Section: Municipal Water Supply In Ahmedabadmentioning
confidence: 99%
“…This has been the Government of Gujarat’s primary response to the issue of water scarcity for domestic and industrial use, replacing local dam—and groundwater—based schemes across the state.' (Luxion 2017 ). Mehta and Mehta ( 2011 ) had showed that with water from the Narmada River reaching the interiors of Kutch, North Gujarat and Suarashtra, and the Government of Gujarat’s priority to water sector, there is increased drinking water security in the state.…”
Section: Introductionmentioning
confidence: 99%